Het die Reformasie die leer gered en aanbidding verloor? - B. Spoelstra (Acta Theologica)
Little information is available on the relation between doctrine and liturgy during and after the Reformation. The concept “doctrine” relates to what is, since Emanuel Kant, labelled as theory and “liturgy” refers to practice as if these concepts were not related. This article investigates the validity of this perception. It asserts that this may be true in a tradition in the wake of Zwingli’s reformation, and concludes that liturgy must be subservient to what the congregation believes (doctrine) otherwise liturgy impedes on religious and sacramental belief and experience. Afrikaans Churches inherited doctrine and liturgy from the Reformed Churches in the Netherlands who followed the liturgical concepts of Zwingli. The latter rejected the concept that Christ is present in holy communion, and confined his liturgy to the Roman pedagogical pronaus (pre-mass). Zwingli’s liturgy (prayer, etc.) is dominated by a pedagogical sermon (good or bad) by a trained minister (dominus). He viewed the Lord’s Supper as an objective way of preaching the sacrifice and atonement on Calvary and not as a covenantal communion. He restricted this celebration to four times a year. By contrast, Roman and Eastern Orthodox Churches thrived because liturgy served their confessions of faith. Calvin followed the custom of the ancient churches, the structure of the Missa Romanun and absolute unity between Word and Sacrament. He was not allowed to realise his liturgical concepts (except singing Psalms) in Geneva. In the current struggle for “liturgical renewal” in reformed churches in South Africa the indissoluble relation between faith (doctrine) and experiencing and expressing faith (liturgy) should be restored and utilised in order to succeed and survive.